Numerical Investigation of Pollutant Transport in a Realistic Terrain with the SPH-SWE Method - Tian, Lirong; Gu, Shenglong; Wu, Yushuai; Wu, Haitao; Zhang, Chi (Frontiers in Environmental Science, 2022)
A large amount of wastewater from industrial and urban residents enters rivers and lakes through the sewage outlet, causing the deterioration of water quality near the sewage outlet. The smoothed particle hydrodynamics (SPH) formulation based on the open-source Fortran code SPHysics is extended to solve the advective-diffusion for the evolution of the pollution distribution with shallow water equation (SWE). Several numerical cases, such as uniform flow, dam-break flows in one and two dimensions, are studied to verify the accuracy of the present SPH-SWE diffusion model. The results are in good agreement with the analytical solutions. The concentration of negative value and oscillation could be avoided. It demonstrates that the present SPH-SWE diffusion model has good stability and reliability for solving the pollutant transport equation. The actual terrain case is also simulated to predict the concentration distribution of the river. The concentration is distributed in the center of the Nanmenxia river where the flow velocity is relatively high. The simulation results are reasonable, implying that it has great potential in predicting the diffusion process of pollutants in the actual terrain.